A series of V-shaped small molecule non-fullerene electron acceptors for efficient bulk-heterojunction devices. (December 2019) - Rao, Pedada S.; More, Vishal G.; Jangale, Asha D.; Bhosale, Sheshanath V.; Bhosale, Rajesh S.; Puyad, Avinash L.; Chen, Jing-Yu; Li, Jing-Liang; Bhosale, Sidhanath V.; Gupta, Akhil; Sharma, Ganesh D.
Abstract: Two simple semiconducting acceptor-acceptor1 -donor-acceptor (A-A1 -D-A) modular, small molecule non-fullerene electron acceptors, 2-(4-(7-hexadecyl-1, 3, 6, 8-tetraoxo-3, 6, 7, 8-tetrahydrobenzo[ lmn ][3, 8]phenanthrolin-2(1 H )-yl)phenyl)-3-(6-((4-(7-hexadecyl-1, 3, 6, 8-tetraoxo-3, 6, 7, 8-tetrahydrobenzo[ lmn ][3, 8]phenanthrolin-2(1 H )-yl)phenyl)ethynyl)-9-octyl-9 H -carbazol-3-yl)buta-1, 3-diene-1, 1, 4, 4-tetracarbonitrile (NDICz-5 ) and 2-(4-(3, 3-dicyano-2-(4-(7-hexadecyl-1, 3, 6, 8-tetraoxo-3, 6, 7, 8-tetrahydrobenzo[ lmn ][3, 8]phenanthrolin-2(1 H )-yl)phenyl)-1-(6-((4-(7-hexadecyl-1, 3, 6, 8-tetraoxo-3, 6, 7, 8-tetrahydrobenzo[ lmn ][3, 8]phenanthrolin-2(1 H )-yl)phenyl)ethynyl)-9-octyl-9 H -carbazol-3-yl)allylidene)cyclohexa-2, 5-dien-1-ylidene)malononitrile (NDICz-6 ), were designed, synthesized and characterized for application in solution-processable bulk-heterojunction solar cells. The optoelectronic and photovoltaic properties ofNDICz-5 andNDICz-6 were directly compared with those of a structural analogue, 7, 7'-(((9-octyl-9 H -carbazole-3, 6-diyl)bis(ethyne-2, 1-diyl))bis(4, 1-phenylene))bis(2-hexadecylbenzo[ lmn ][3, 8]phenanthroline-1, 3, 6, 8(2 H, 7 H )-tetraone) (NDICz-4 ), which was designed based on an A-D-A format. All of these new materials were designed to be V-shaped and comprised an electron rich carbazole donor core (D) together with electron deficient naphthalene diimide terminal core (A). In the simple A-D-A system, naphthalene diimide was the terminal functionality, whereas in the A-A1 -D-A system, tetracyanoethylene (TCNE) and tetracyanoquinodimethane (TCNQ) derived functionalities were incorporated as A1 units by keeping D/A units constant. The inclusion of A1 was mainly done to induce cross-conjugation within the molecular backbone and hence to improve light-harvesting. The physical and optoelectronic properties were characterized by ultraviolet–visible, thermogravimetric analysis, photo-electron spectroscopy in air and cyclic voltammetry. These new materials exhibited energy levels complementing those of the conventional donor polymer poly(3-hexyl thiophene) (P3HT). Solution-processable bulk-heterojunction devices were fabricated withNDICz-4, NDICz-5 andNDICz-6 as non-fullerene electron acceptors. Studies on the photovoltaic properties revealed that the best P3HT:NDI-Cz6 -based device showed an impressive enhanced power conversion efficiency of 7.58%, an increase of around two-fold with respect to as-cast blend, after solvent vapor annealing using carbon disulfide. Not only are the results among the best in the current literature using the conventional donor polymer P3HT, but clearly demonstrate that A-A1 -D-A type, V-shaped small molecules are promising non-fullerene acceptors in the research field of organic solar cells. Graphical abstract: Image 1 Highlights: The first V-shaped non-fullerene electron acceptors: combined carbazole and naphthalenediimide bridged by TCNE and TCNQ units. Creation of A-A1 -D-A design using Cz and NDI, and TCNE/TCNQ units. Direct comparison of A-A1 -D-A and A-D-A designs in terms of optoelectronic and photovoltaic properties. The inclusion of TCNE and TCNQ units is to induce cross-conjugation within the backbone, thus, to improve light-harvesting. NDICz-6 afforded the highest efficiency of 7.58% using the conventional donor polymer (P3HT) after the solvent vapor annealing.